Neoconstitutionalism - Pozzolo, Susanna (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
The word ’neoconstitutionalism’ presented wants to offer a very synthetic information about the origin, development and dissemination of ‘neoconstitucionalist’ doctrine. As a part of the interpretative turn of the past and present century, the doctrine is developed, on the one hand, as a critique of doctrinal positions as the ’positivism’ or ’formalism’ and, on the other hand, as a reflective philosophical doctrine toward potentialities offered by the large number of rights and values recognized in the constitutional texts which are produced from the second postwar. The entry, emphasizing the theoretical features of neoconstitutionalism, wants to present briefly also the motives and the reasons behind its development, showing the theoretical, moral and political implications. doi: http://dx.doi.org/10.20318/eunomia.2016.3284